Biomarkers of Prognosis and Efficacy of Anti-angiogenic Therapy in Metastatic Clear Cell Renal Cancer - D'Aniello, Carmine; Berretta, Massimiliano; Cavaliere, Carla; Rossetti, Sabrina; Facchini, Bianca Arianna; Iovane, Gelsomina; Mollo, Giovanna; Capasso, Mariagrazia; Pepa, Chiara Della; Pesce, Laura; D'Errico, Davide; Buonerba, Carlo; et al. (Frontiers in Oncology, 2019)
In the last decades, the prognosis of metastatic renal cell carcinoma (mRCC) has remarkably improved following the advent of the “targeted therapy” era. The expanding knowledge on the prominent role played by angiogenesis in RCC pathogenesis has led to approval of multiple anti-angiogenic agents such as sunitinib, pazopanib, axitinib, cabozantinib, sorafenib and bevacizumab. These agents can induce radiological responses and delay cancer progression for months or years before onset of resistance, with a clinically meaningful activity. The need for markers of prognosis and efficacy of anti-angiogenic agents has become more compelling as novel systemic immunotherapy agents have also been approved in RCC and can be administered as an alternative to angiogenesis inhibitors. Anti PD-1 monoclonal antibody nivolumab has been approved in the second-line setting after tyrosine kinase inhibitors failure, while combination of nivolumab plus anti CTLA-4 monoclonal antibody ipilimumab has been approved as first-line therapy of RCC patients at intermediate or poor prognosis. In this review article, biomarkers of prognosis and efficacy of antiangiogenic therapies are summarized with a focus on those that have the potential to affect treatment decision-making in RCC. Biomarkers predictive of toxicity of anti-angiogenic agents have also been discussed.